Biografia músico-educativa: produção de sentidos em meio à teia da vida - Almeida, Jéssica de (2019)
This research, linked to the Programa de Pós-graduação em Educação (PPGE) from the Universidade Federal de Santa Maria (UFSM), line of Arts and Education Research (LP4) and the NarraMus Research Group – Auto-narratives in Musical Practices, aimed to comprehend the ways through which musical-educational biographies developed by Music undergraduates create meaning to their formation process in undergraduate school. To do so, the study was delineated with three specific goals: a) to discuss collectively the narratives produced during the development of a musical-educational biography; b) to analyze the process which resulted in musical-educational biographies produced by the students from Jossos’s (2010b) Retroactive Spiral of the Way to Self and; c) to bring together personal and academic experiences as from the study about the formation processes, pondering on the interrelations present in individual and collective narratives constructions of the research subjects. With a (auto)biographic approach, the research was conducted upon the story of life biographic method and analyzed self-narratives (musical) and intertwined narratives produced by the musical-educational biography. The analysis of such production was guided by Jossos’s (2010b) Retroactive Spiral of the Way to Self and consisted of studying, firstly, the comprehension marks of the formation process and, later, of evidencing the learning and knowledge genres (JOSSO, 2004). The research revealed that a) the development and study of musical-educational biographies allowed comprehending that the academic formation processes make sense from the experiences of musical learning in religious contexts and day-to-day musical learning and non-formal; b) the learning and instrumental and pragmatic knowledge, acquired throughout life, sometimes, are silent, mainly when contested through contact with more formal, institutionalized knowledge; c) the formation knowledge, the learning and comprehensive and explicative knowledge, although not aware by part of the research subjects, operate as true refugees, in which they seek subsidies to understand how much they do know or do not know in undergraduate school and d); the aware process were perceived, mainly, regarding the learning and existential knowledge, to the dynamics, attitudes and characteristics of the subjects. The Higher Education registers, in some life stories, as a crucial moment of reorientation and change, this seen as an opportunity to learn right, a possibility to open the whole range of professional possibilities, a place of self- (re)affirmations, in some cases, and true posture change in others.